S.A. Yesenin’s Diptich about the Sound “Under the Red Elm, the Porch and the Yard...” and “Your Voice is Invisible, Like Smoke in a Hut...”: Context, Poetics, Dating - Svetlana A. Seregina (Studia Litterarum)
The article is devoted to the revision of the conditional dating of S.A. Yesenin’s poem “Under the red elm, the porch and the yard...” (1917) accepted in the Complete Works of S.A. Yesenin (1995–2002). The work introduces on evidentiary grounds a number of previously unknown sources of Yesenin’s ideas about the life-creating nature of sound. The study also presents the results of textual analysis of the white autograph of S.A. Yesenin’s poem “Under the red elm, the porch and the yard...”. These searches allowed us to challenge A.A. Kozlovsky’s arguments, who dated the poem “Under the red elm porch and yard...” to 1917, on documentary grounds. The author of the article proposes revise the dating of this work in favor of 1916 on the basis of a comparative analysis with another poem — “Your voice is invisible, like smoke in a hut...” (1916). This analysis demonstrates the artistic-philosophical, metrical and compositional unity of the two works, due to the general context and specific sources. This unity allows us to speak of the poems “Under the red elm, the porch and the yard...” and “Your voice is invisible, like smoke in a hut...” as a diptych created in 1916.